Health and social responses to drug problems : a european guide - Observatorio Europeo de las Drogas y las Toxicomanías (Lisboa) (Publications Office of the European Union, 2017)
This guide and the associated package of online materials provides a reference point for those planning or delivering health and social responses to drug problems in Europe. The most appropriate responses will depend on the specific drug problems, the contexts in which these occur and the types of intervention that are possible and socially acceptable. By providing key information on some of the most important drug issues for Europe and the responses available, this guide aims to assist those involved in tackling these challenges to develop new programmes and improve existing ones